CRF1 and ACTH inhibitors are a promising approach to treat obesity and leptin and insulin resistance - Contreras, Patricio H.; Falhammar, Henrik (Frontiers in Endocrinology, 2025)
Evidence synthesisObesity is a state of subtle hypercortisolism accompanied by leptin and insulin resistance. Serum total cortisol concentration is normal or slightly subnormal in obese subjects. However, they have high cortisol production rates. Reduced concentrations of serum cortisol-binding globulin caused by hyperinsulinemia explain this paradox. Elevated free cortisol concentrations act on the adipose cells of these patients due to excess adrenal cortisol secretion, as well as to high adipocyte expression of 11-beta-hydroxysteroid dehydrogenase type 1 (11β-HSD1). CRF1 and ACTH blockers (such as crinecerfont and atumelnant, respectively) may replace leptin action on the adrenal axis by reducing adrenal cortisol excess in individuals with obesity.ContextIndividuals with obesity experience a subtle hypercortisolism secondary to leptin resistance. Weight loss is commonly followed by a weight rebound, likely provoked by residual leptin resistance. Since leptin inhibits the adrenal axis, leptin resistance induces a hypersecretion of cortisol, promoting chronic, pathological lipolysis of white adipose tissue. The latter situation leads to lean organ steatosis, muscle and liver insulin resistance, and β-cell apoptosis. So, there is an urgent need to restore adrenal inhibition in obese individuals.Evidence acquisitionWe searched PubMed articles and included them if relevant.ConclusionsIndividuals with obesity and high levels of adipose insulin resistance may benefit from CRF1/ACTH inhibitors, reducing ACTH secretion or its action. A reduction in their adipose resistance index may lead to diminished lean organ steatosis and reduced appetite due to a decrease in orexigenic signals, mainly free cortisol and insulin.